A survey of the extent of information technology applications among six medical school libraries in Metro Manila - Tantiongco, Roman Gregorio G. (Institute of Library Science, University of the Philippines Diliman, 1996)
The survey is an initial attempt to ascertain the levels of library automation among medical school libraries in Metro Manila. Library automation is discussed using the parameters of library information systems, CD-ROM applications, remote database access, networking and Internet connection and access. A brief portion on network planning is also presented at the latter part of the study.